2006
DOI: 10.1534/genetics.105.052704
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hyphal Morphogenesis and the DNA Damage Response by the Aspergillus nidulans ATM Homolog AtmA

Abstract: Ataxia telangiectasia (A-T) is an inherited disorder characterized by progressive loss of motor function and susceptibility to cancer. The most prominent clinical feature observed in A-T patients is the degeneration of Purkinje motor neurons. Numerous studies have emphasized the role of the affected gene product, ATM, in the regulation of the DNA damage response. However, in Purkinje cells, the bulk of ATM localizes to the cytoplasm and may play a role in vesicle trafficking. The nature of this function, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0
5

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 48 publications
(44 reference statements)
6
32
0
5
Order By: Relevance
“…As was previously seen (Malavazi et al 2006(Malavazi et al , 2007, and this work), the DatmA mutant strain showed decreased polar growth when compared to the wild-type strain (Table 4). The DchkA and DchkB mutant strains have not displayed polar growth defects while the double-mutant DchkA DchkB had decreased polar growth.…”
Section: Strains and Media Methodssupporting
confidence: 88%
See 2 more Smart Citations
“…As was previously seen (Malavazi et al 2006(Malavazi et al , 2007, and this work), the DatmA mutant strain showed decreased polar growth when compared to the wild-type strain (Table 4). The DchkA and DchkB mutant strains have not displayed polar growth defects while the double-mutant DchkA DchkB had decreased polar growth.…”
Section: Strains and Media Methodssupporting
confidence: 88%
“…As previously shown by Malavazi et al (2006Malavazi et al ( , 2007, the DatmA mutant strain has an accelerated rate of proliferation, i.e., increased nuclear kinetics, when compared to the wild-type strain ( Figure 2B, first and second lanes). The double mutant showed an increased number of nuclei that was comparable to the DatmA mutant strain ( Figure 2B, third lane).…”
Section: Strains and Media Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…This is because the sonB1 mutation is not synthetically lethal in combination with mutations in other cell cycle checkpoint regulators, including the A. nidulans orthologs of ATR, ATRIP, ATM, or the cdc2F mutant (Ye et al 1997;De Souza et al 1999;Hofmann and Harris 2000;Malavazi et al 2006). In addition, given that the sonB1 mutant was viable when combined with these cell cycle checkpoint mutants or the uvsC Rad51 .…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate this, we determined if sonB1 mutants genetically interacted with mutants defective in different aspects of the DNA damage response in A. nidulans (Kafer and Mayor 1986;Yoon et al 1995;Kafer and May 1997;van Heemst et al 1997;Ye et al 1997;De Souza et al 1999;Hofmann and Harris 2000;Bruschi et al 2001;Semighini et al 2003;Malavazi et al 2006;Nayak et al 2006). Most striking were the genetic interactions between sonB1 and mutants of the A. nidulans NBS1 ortholog scaA NBS1 (Bruschi et al 2001).…”
Section: And (N) Uvsh304mentioning
confidence: 99%